Paradoxical Embolization of the Bilateral Subclavian Arteries After High Tibial Osteotomy. (August 2019) - Miyake, Takahito; Obayashi, Osamu; Kanda, Akio; Okada, Hideshi; Ogura, Shinji; Kaneko, Kazuo
Abstract : A patent foramen ovale provides a portal through which a thrombus might pass from the right side of the circulation to the left. A 65-year-old man underwent high tibial osteotomy after the diagnosis of the right knee osteoarthritis. On postoperative day 12, he developed bilateral arm paresthesia. Enhanced CT revealed emboli in the bilateral pulmonary and subclavian arteries and deep vein thrombosis in the left lower limb. Transesophageal echocardiography after treatment revealed a patent foramen ovale during the Valsalva maneuver. It was thought that bilateral arm paresthesias were caused by the arterial emboli in the bilateral subclavian arteries.